Project proposal : to construct and manage Moya weKhaya - spirit of home : a cultural centre in Khayelitsha, Cape Town - Wright, Yolande (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2008.